Exploring the impact of e-portfolio on esl students’ writing skills through the lenses of malaysian undergraduates - Wirawati Ngui Yi Xe; Vincent Pang; Wendy Hiew; Lee Kean Wah (CALL-EJ, 2020)
This study explored the impact of implementing e-Portfolio as an assessment tool at a public university in Malaysia. It aimed to investigate how the use of the e-Portfolio in an advanced English course contributed to undergraduate students' writing skills. A case study approach was applied whereby open-ended questionnaires and interviews were used to collect qualitative data. A total of 46 students participated in the study. All 46 students answered the questionnaires and 18 of them volunteered for interviews. Online discourses were also included to support the findings where relevant. The data were imported to NVivo 12 and thematic analysis was used as the primary method of data analysis. The findings demonstrated that the use of the e-Portfolio with emphasis on feedback and communication, artefacts and reflections, and peer review contributed positively to the students’ writing skills. Instructor feedback and communication enabled the students to receive detailed information to improve their writing. The inclusion of artefacts led the students to better understand their work and promote reflective practice. Peer review allowed the students to obtain peer support and explore others’ work. The study demonstrated that e-Portfolio is a relevant tool that can provide an enhanced assessment experience for second language learners.